Cytochrome P450 destruction by benzene metabolites 1,4-benzoquinone and 1,4-hydroquinone and the formation of hydroxyl radicals in minipig liver microsomes - Kondrová, Eliška; Stopka, Pavel; Souček, Pavel (Toxicology in vitro, 2007)
Reactive metabolites of benzene 1,4-benzoquinone and 1,4-hydroquinone exert their toxic effects through covalent and/or oxidative damage to DNA and proteins. Since minipigs have been proposed as a suitable model species in toxicological and pharmacological research, the aim of this study was to explore mechanisms by which catechol, 1,4-hydroquinone and 1,4-benzoquinone destroy cytochrome P450 (P450) and induce oxidative stress in minipig liver microsomes. Our second goal was to assess the usefulness of minipig liver microsomes as a model system for the testing of the production of oxidative stress by clinically relevant quinone-containing compounds, e.g. anthracyclines. Of the three benzene metabolites tested, the highest P450 destruction was caused by 1,4-benzoquinone. This destructive effect did not correlate with the production of hydroxyl radicals as measured by ESR spin trapping which was the highest in samples containing 1,4-hydroquinone. Our results confirm previous findings that 1,4-benzoquinone exerts its effect mainly by direct attack on macromolecules while 1,4-hydroquinone rather stimulates the production of reactive oxygen species. Doxorubicin stimulated the production of hydroxyl radicals and the destruction of P450 similarly as 1,4-hydroquinone. Minipig liver microsomes should be further tested as a possibly suitable model system for the testing of potential modulators of the toxicity of doxorubicin.
Keywords: doxorubicin; orchiektomie; vztahy mezi strukturou a aktivitou; elektronová paramagnetická rezonance; Hydroquinones; systém (enzymů) cytochromů P-450; Structure-Activity Relationship; Antimetabolites, Antineoplastic; zvířata; Financing, Organized; oxidační stres; Algorithms; hydroxylový radikál; financování organizované; benzen; Lipid Peroxidation; benzochinony; mužské pohlaví; Cytochrome P-450 CYP3A; miniaturní prasata; Orchiectomy; elektroforéza v polyakrylamidovém gelu; Cytochrome P-450 CYP2E1; Swine; hydrochinony; Oxidative Stress; Electrophoresis, Polyacrylamide Gel; prasata; cytochrom P-450 CYP2E1; Electron Spin Resonance Spectroscopy; peroxidace lipidů; Animals; NADP; jaterní mikrozomy; protinádorové antimetabolity; Benzene; Doxorubicin; Benzoquinones; inhibitory cytochromu P450; Swine, Miniature; Hydroxyl Radical; Cytochrome P-450 Enzyme System; Male; algoritmy; Cytochrome P-450 Enzyme Inhibitors; Microsomes, Liver; cytochrom P-450 CYP3A